Risk Factors and Prevention Strategies for Recurrent Lower Urinary Tract Infections in Pregnant Women: A Literature Review - Mutiara Andjani Arsyad; Amelia Abdullah; Asrini Safitri; M. Hamsah; Abadi Aman (Journal La Medihealtico, 2026)
Urinary tract infections (UTIs) in pregnant women are among the most common health problems and may lead to serious complications for both the mother and the fetus. Physiological changes during pregnancy increase the risk of infection as well as recurrence of UTIs. Therefore, a comprehensive understanding of risk factors and effective preventive strategies is essential. This study aims to analyze the risk factors and preventive measures for recurrent UTIs in pregnant women based on current literature. This study employed a narrative review approach by examining various scientific articles obtained from databases including PubMed, ScienceDirect, Google Scholar, Garuda, and Neliti. The literature search was conducted using keywords relevant to the research topic. Results of the research showed that the main risk factors for UTIs in pregnant women include hormonal and anatomical changes, a history of previous UTIs, poor personal hygiene, sexual activity, and medical conditions such as diabetes mellitus. In addition, asymptomatic bacteriuria plays an important role in increasing the risk of complications. Effective preventive measures include routine screening, culture-based treatment of urine samples, health education, and the implementation of clean and healthy lifestyle practices. The occurrence and recurrence of UTIs in pregnant women are multifactorial in nature, requiring a comprehensive management approach to reduce risks and improve maternal and fetal health outcomes.